Comparative Evaluation of Non-Protein Nitrogenous Compounds in Fishes of Fresh and Brackish Water Environments - Raju, Chintu M; Mathew, Suseela; Mathew, Mathen (Fishery Technology, 2025)
Quantitative comparison of the non-protein nitrogen (NPN) fractions viz., alpha-amino nitrogen, peptides, trimethylamineoxide (TMAO) and free amino acids from muscles of reared fishes of fresh and brackish water environments is attempted. Compared to fishes from the brackish water environments, those from the fresh water showed higher NPN content. Among the fresh water fishes, Labeo rohita accounted for maximum NPN content viz., 17.11% of the total nitrogen. Minimum values of peptides were recorded for Hypophthalmichthys molitrix and maximum for Labeo rohita. TMAO could not be detected in any fresh water fish. Maximum values for alpha-amino nitrogen were obtained for Liza macrolepis and Labeo rohita. Etroplus suratensis, collected from brackish water and fresh water environments showed significantly different peptide and TMAO values (p